Back to Back: A Focus on Reducing the Logistics Costs and Tax - Rogério João Lunkes; Fernando Rodrigo Sagaz (Revista Sociedade, Contabilidade e Gestão, 2012)
The objective is to identify the main aspects related to the operation of Back to Back set out in international trade, which enables reduction of logistics costs and taxes. The operation of Back to Back is an excellent opportunity to increase foreign exchange gain and offer greater flexibility to commercial operations that the business requires. The methodology used in preparing this study was qualitative research according to the characteristics and nature of the problem. From the use of descriptive research study aims to demonstrate the main theoretical aspects underlying the subject in reference. This study aimed to identify the main aspects related to the operation of Back to Back set out in international trade and tax effects in an organization and logistics of industrial electronics segment of the State of Santa Catarina. The study demonstrated that the benefits of the operation of Back to Back is of paramount importance for companies having a positive impact in financial terms by reducing the need for tax payments and logistics costs which affect the processes of import and export. The results presented showed that the company studied the operation of Back to Back is essential for international negotiations.